1998
DOI: 10.1055/s-2007-1010255
|View full text |Cite
|
Sign up to set email alerts
|

Results after Surgery in Stage-I Bronchogenic Carcinoma

Abstract: 5-year survival of our patients was in the range reported in literature. Most patients died of distant metastases. Our retrospective study probably underestimated the occurrence of second primary cancers of the lung. Limited resection in poor-risk patients showed equivalent results to lobectomy. The extent of lymph-node resections had no influence on survival of stage-I patients, however, it must be remembered that positive results in lymph nodes shift patients to higher stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 5 publications
(5 reference statements)
3
7
0
Order By: Relevance
“…The risk from pulmonary resection is dependent on the extent of resection. In that way, it is important to point out that the proportion of patients having undergone a pneumonectomy was about 13% in the present series, a rate that is in accordance with what is usually reported in this early stage, ranging from 5 to 20% [6,7,[17][18][19][20]. Of concern is the fact that the technique of lymph node sampling did not influence postoperative mortality or major morbidity accordingly to previous claims [5,7], but in contrast with others [1].…”
Section: Discussionsupporting
confidence: 89%
“…The risk from pulmonary resection is dependent on the extent of resection. In that way, it is important to point out that the proportion of patients having undergone a pneumonectomy was about 13% in the present series, a rate that is in accordance with what is usually reported in this early stage, ranging from 5 to 20% [6,7,[17][18][19][20]. Of concern is the fact that the technique of lymph node sampling did not influence postoperative mortality or major morbidity accordingly to previous claims [5,7], but in contrast with others [1].…”
Section: Discussionsupporting
confidence: 89%
“…Tumor stage, performance status and weight loss at the time of diagnosis have been found tohave a negative impact on patient survival from NSCLC in previous research [34,35]. The present study confirmed that advanced cancer stage and poor performance status were prognostic factors for NSCLC survival.…”
Section: Discussionsupporting
confidence: 88%
“…20 Many but not all studies of positive margins of surgically treated lung cancers have shown adverse impact by residual disease. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Microscopic residual tumor at the bronchial resection margin has then been divided into different patterns. Cotton 1 first divided microscopic residual disease into mucosal tumor (spreading from a mucosal lesion), and extramucosal microscopic residual disease (tumor involving peribronchial soft tissues or tumor within lymphatics).…”
Section: Discussionmentioning
confidence: 99%
“…To this end, resection margins should be uninvolved with tumor. Many surgical series have demonstrated adverse patient outcome with either microscopic or macroscopic residual tumor at the bronchial resection margin, [1][2][3][4][5][6][7][8][9][10][11][12][13] and thus it is usually assumed that negative margins give the best chance for local control. However, poor outcomes with residual microscopic disease have not been reported by all authors.…”
mentioning
confidence: 99%